IAEA Isotope-enabled coupled catchment–lake water balance model, IWBMIso: description and validation†. Issue 4 (3rd July 2016) - Belachew, Dagnachew Legesse; Leavesley, George; David, Olaf; Patterson, Dave; Aggarwal, Pradeep; Araguas, Luis; Terzer, Stefan; Carlson, Jack
ABSTRACT: The International Atomic Energy Agency (IAEA) Water Balance Model with Isotopes (IWBMIso) is a spatially distributed monthly water balance model that considers water fluxes and storages and their associated isotopic compositions. It is composed of a lake water balance model that is tightly coupled with a catchment water balance model. Measured isotope compositions of precipitation, rivers, lakes, and groundwater provide data that can be used to make an improved estimate of the magnitude of the fluxes among the model components. The model has been developed using the Object Modelling System (OMS). A variety of open source geographic information systems and web-based tools have been combined to provide user support for (1) basin delineation, characterization, and parameterization; (2) data pre-processing; (3) model calibration and application; and (4) visualization and analysis of model results. In regions where measured data are limited, the model can use freely available global data sets of climate, isotopic composition of precipitation, and soils and vegetation characteristics to create input data files and estimate spatially distributed model parameters. The OMS model engine and support functions, and the spatial and web-based tool set are integrated using the Colorado State University Environmental Risk Assessment and Management System (eRAMS) framework. The IWBMIso can be used to assess the spatial and temporal variability of annual and monthly water balance components for input to water planning and management.